Numerical Simulation of Rock Uniaxial Compressive Strength and Deformation Failure Law under Different Size Conditions - Zhichao Tian; Chunan Tang; Hao Li; Hui Xing; Xiangda Ning (Advances in Civil Engineering)
Rock engineering occupies an important position in the 21st century. In the face of rock engineering disasters, we are only looking for the essential problems through experiments on rocks, but rock experiments cannot be realized in large numbers, so the article uses numerical simulation software RFPA (Realistic Failure Process Analysis) 2D Basic to simulate rock under different size conditions numerically. In this paper, a rock model with a diameter of 50 mm is used for simulation research. Meanwhile, five calculation models of height-to-diameter ratios of 1.0, 1.5, 2.0, 2.5, and 3 are used. Through simulation calculation, we find that the rock model failure is more than complicated when the value of the height-to-diameter ratio is exceedingly low (1), but as the height-to-diameter ratio increases, the failure mode will become simpler. The stress-concentrated failure will be in the form of axial failure. When the height-to-diameter ratio increases (1.5–2), other damage cracks appear on the basis of axial cleavage failure. As the height-to-diameter ratio continues to increase (about 2.5), only shear failure occurs. When the height-to-diameter ratio reaches a relatively high level (3), there will be both axial rip and other damage. When the height-to-diameter ratio is oversize, there will be both axial rip failure and end damage.